2020
DOI: 10.1097/md.0000000000020952
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of urinary tract infection in acute stroke patients

Abstract: Patients with stroke have a high risk of infection which may be predicted by age, procalcitonin, interleukin-6, C-reactive protein, National Institute of Health stroke scale (NHSS) score, diabetes, etc. These prediction methods can reduce unfavourable outcome by preventing the occurrence of infection. We aim to identify early predictors for urinary tract infection in patients after stroke. In 186 collected acute stroke patients, we divided them into urinary tract infection group, other in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 106 publications
0
9
0
1
Order By: Relevance
“…However, an elevated PCT should be evaluated carefully by the clinicians, especially in fragile people, because its value accurately predicts the presence of bacteraemia and bacterial load [16] and seems correlated to disease severity [14,15], regardless of the origin of the primary infection. Finally, three studies showed low accuracy and neglectable PCT changes in lower UTIs [12,14,15]. Those results suggest a marginal role of PCT during lower UTIs and seem congruent with the idea that PCT increases significantly during bacteremia.…”
Section: Procalcitoninmentioning
confidence: 58%
See 1 more Smart Citation
“…However, an elevated PCT should be evaluated carefully by the clinicians, especially in fragile people, because its value accurately predicts the presence of bacteraemia and bacterial load [16] and seems correlated to disease severity [14,15], regardless of the origin of the primary infection. Finally, three studies showed low accuracy and neglectable PCT changes in lower UTIs [12,14,15]. Those results suggest a marginal role of PCT during lower UTIs and seem congruent with the idea that PCT increases significantly during bacteremia.…”
Section: Procalcitoninmentioning
confidence: 58%
“…UTIs induce a significant increase in serum IL-6, and its level could differentiate lower and upper UTIs. Unfortunately, only two small studies evaluated this aspect and in two different clinical settings [15,21] Urine IL-6 was explored by eleven small studies [11,12,15,[19][20][21][22][23][26][27][28], usually performed in the elderly. Not all studies suggested a significant increase in urine IL-6 during UTIs, and the studies were too heterogenous to obtain a univocal recommendation.…”
Section: Interleukin-6mentioning
confidence: 99%
“…The hemoglobin peptide library can produce different biological effects, which include antimicrobial hemoglobin-derived peptides. Then, the antimicrobial hemoglobin-derived peptides can produce antibacterial effects, thereby reducing inflammation caused by microbial infections ( 28 , 29 ). Therefore, the requirement for RBC infusion was also included in our nomogram as a risk factor for infection.…”
Section: Discussionmentioning
confidence: 99%
“…Six articles (8)(9)(10)(11)(12)14) examined whether patient age had an effect on HAP infection. There were 301 HAP cases and 809 non-HAP cases.…”
Section: Agementioning
confidence: 99%
“…Six articles (8)(9)(10)(11)(12)14) examined the effect of NIHSS score at admission on the occurrence of HAP. There were 301 HAP cases and 809 non-HAP cases.…”
Section: Nihss Scorementioning
confidence: 99%